2010
DOI: 10.1126/science.1190929
|View full text |Cite
|
Sign up to set email alerts
|

Changing Face of Microglia

Abstract: Microglia are resident brain cells that sense pathological tissue alterations. They can develop into brain macrophages and perform immunological functions. However, expression of immune proteins by microglia is not synonymous with inflammation, because these molecules can have central nervous system (CNS)-specific roles. Through their involvement in pain mechanisms, microglia also respond to external threats. Experimental studies support the idea that microglia have a role in the maintenance of synaptic integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
409
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 536 publications
(420 citation statements)
references
References 53 publications
7
409
0
4
Order By: Relevance
“…On the basis of these observations, researchers have sought a potential explanation for why an organism might expend considerable energy to continuously scan the neuropil under homeostatic conditions. As a result, several groups have argued that microglia might have an essential role in monitoring synaptic activity Graeber, 2010;Kettenmann et al, 2013;. In support of this hypothesis, ultrastructural analysis in mice has revealed that microglial processes make direct contact not only with axon terminals and dendritic spines but also astrocytes and their perisynaptic processes that ensheath dendritic branches (Tremblay et al, 2010).…”
Section: Microgliamentioning
confidence: 98%
“…On the basis of these observations, researchers have sought a potential explanation for why an organism might expend considerable energy to continuously scan the neuropil under homeostatic conditions. As a result, several groups have argued that microglia might have an essential role in monitoring synaptic activity Graeber, 2010;Kettenmann et al, 2013;. In support of this hypothesis, ultrastructural analysis in mice has revealed that microglial processes make direct contact not only with axon terminals and dendritic spines but also astrocytes and their perisynaptic processes that ensheath dendritic branches (Tremblay et al, 2010).…”
Section: Microgliamentioning
confidence: 98%
“…Microglial activation may also be a response to neuronal loss as well as to neuronal dysfunction and their extremely low activation threshold results in their almost universal involvement in even subtle brain pathologies [41]. So in neurodegenerative diseases, widespread microglial activation may reflect widespread neuronal dysfunction in addition to the more apparent alterations of synapses.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Although microglia can express ''immune molecules'', this is not synonymous with inflammation, since these molecules can have CNS-specific roles independent of their roles in the immune or inflammatory response [41]. Similarly, molecules known to neurobiology, including gamma amino butyric acid and the lens protein alpha B crystallin can have intriguing and distinct functions in the immune system [47].…”
Section: Role Of Microglia In Normal Brainmentioning
confidence: 99%
“…They actively move their branched processes to sense pathological alterations or disturbances to ultimately maintain CNS homeostasis [1][2][3][4]. Once abnormalities are detected, microglia dramatically transform into a reactive phenotype through a progressive series of cellular and molecular changes, including morphological hypertrophy, proliferation, and the expression of various genes [3,5].…”
Section: Introductionmentioning
confidence: 99%